Produktywność pracy - problemy pomiaru i wykorzystania w przedsiębiorstwie - Gableta, Małgorzata; Maksimowicz, Zofia (Labor Productivity - Measure and Application Problems in Enterprise, 2005)
The paper presents recent problems, connected with labor productivity indicators. The attention was drown to verification of the previously proved productivity indicators, especially in the field of costs and effects. The empirical research, presented in the article, has shown the applications of labor productivity indicators in the business practice
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1061, s. 89-95